Pemanfaatan Limbah Rumah Tangga Sebagai Pupuk Organik Di Lahan Pertanian Kelurahan Jrebeng Kulon - Syafi'i, Abdur Rahman; Sugiarto, Totok; Wulandari, Anita Surya; Putri, Marshela Handoko; Ayyubi, Ahmad Maman (Jurnal Ekonomi Pertanian dan Agribisnis, 2025)
Household waste is a source of environmental pollution, the amount of which is increasing along with population growth and daily community activities. The type of waste produced is mostly food scraps, vegetables, and fruits, which are classified as organic waste. If not managed properly, this waste can cause serious problems, such as unpleasant odors, soil, water, and air pollution, and even become a source of disease. However, household waste has great potential to be reused as environmentally friendly organic fertilizer. This study aims to describe the use of household waste as organic fertilizer in Jrebeng Kulon Village and to examine its impact on the local community's agricultural land. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results show that the community of Jrebeng Kulon Village has processed household organic waste using a simple composting method, using both containers and holes in the ground. The resulting fertilizer has been proven to increase soil fertility, reduce farmers' dependence on chemical fertilizers, and reduce the volume of household waste disposed of in landfills. These findings indicate that the use of household waste as organic fertilizer not only plays a role in maintaining agricultural sustainability but also supports the creation of a healthier and more sustainable environment.